2004
DOI: 10.1016/j.jimonfin.2003.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The credit crunch in East Asia: what can bank excess liquid assets tell us?

Abstract: The paper proposes a two-step approach to assess the extent to which the fall in credit in crisis-stricken East Asian countries was a supply-or demand-induced phenomenon. The first step is based on the estimation of demand function for excess liquid assets by commercial banks. Such a function is derived analytically in the first part of the paper. The second step consists of establishing dynamic projections for the periods following the crisis and assessing whether or not residuals are large enough to be viewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 17 publications
4
56
0
1
Order By: Relevance
“…Consistent with Saxegaard (2006), going beyond acknowledging the threat of increasing inflation, several authors have observed that the abundance of liquidity is likely to have adverse consequences for the ability of monetary policy to influence demand conditions and hence, stabilize the economy 3 . Agénor et al (2004) for instance note that if banks already hold liquidity in excess of requirements, attempts by the monetary authorities to increase liquidity in a bid to stimulate aggregate demand will prove largely ineffective. In the same vein, Nissanke & Aryeetey (1998) argue that in the presence of excess liquidity, it becomes difficult to regulate money supply using the required reserve ratio and the money multiplier, so that the use of monetary policy for stabilization purposes is undermined.…”
Section: Inflation Monetary Policy and African Businessmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with Saxegaard (2006), going beyond acknowledging the threat of increasing inflation, several authors have observed that the abundance of liquidity is likely to have adverse consequences for the ability of monetary policy to influence demand conditions and hence, stabilize the economy 3 . Agénor et al (2004) for instance note that if banks already hold liquidity in excess of requirements, attempts by the monetary authorities to increase liquidity in a bid to stimulate aggregate demand will prove largely ineffective. In the same vein, Nissanke & Aryeetey (1998) argue that in the presence of excess liquidity, it becomes difficult to regulate money supply using the required reserve ratio and the money multiplier, so that the use of monetary policy for stabilization purposes is undermined.…”
Section: Inflation Monetary Policy and African Businessmentioning
confidence: 99%
“…Many other commodity prices also rose sharply over this period: milk powder by 90%, rice by 25% and wheat by 70%. Such large changes in prices have had tremendous impacts on the incomes of poor households in developing countries (FAO, 2007;World Bank 2008;Ivanic & Martin, 2008). incorporate the substantially documented issue of excess liquidity in African financial institutions that weakens monetary policy effectiveness (Saxegaard, 2006;Agénor et al, 2004;Nissanke & Aryeetey, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Also, it shows that the same shock will generate a "cloudy day" under some circumstances and will not under others. 1 Therefore, the policymaker's reaction could be understood as an optimal response to different situations, instead as of "flipping coins".…”
mentioning
confidence: 99%
“…3 This last instrument is the focus of the paper. 1 Continuing with the weather comparison, having one week of rain is a very bad shock if you live in LA (think about finding an indoor place to eat on UCLA's campus!) but it is a normal day in London.…”
mentioning
confidence: 99%
See 1 more Smart Citation